"We are really starving for respect and support," the struggle of Iranian nurses in adhering to professional values: A qualitative study - Sahar Kazemi; Naser Parizad; Hossein Habibzadeh (Wiley, 2023)
Abstract Aims To investigate nurses' experiences of adhering to professional values in clinical settings. Design A qualitative study with a conventional content analysis approach. Methods This study was conducted from January 2021 to March 2022. Semi‐structured interviews were conducted with 12 nurses working in different wards of five public and private hospitals in West Azerbaijan of Iran. Data were analysed using the conventional content analysis approach proposed by Graneheim and Lundman (Nurse education today, 24, 2004, 105) Results "Barriers to nurses' professional values" emerged as the main category of Iranian nurses' experiences in adhering to professional values. Three subcategories of barriers were revealed: "nurses' challenges," "professional suppressors" and "poor working conditions." Conclusion Barriers in clinical settings can overshadow nurses' professional performance and disrupt their adherence to professional values. Nursing managers must pay attention to nurses' challenges, their professional suppressors and poor working condition to help them promote their professional performance in clinical settings. Thus, nursing managers should not neglect the continuous education of nurses to assist them in increasing their clinical skills by holding practical and theoretical workshops. Improving the working conditions and clinical atmosphere by recruiting a capable workforce and applying psychological and financial support for nurses are essential to increase the quality of nursing care.